Faneuil Hall Square, ca. 1888 (Tufts Archival Research Center, 2005)
Street-level view looking west of the Old Corner. This view is of (left to right) 25 and 26 Faneuil Hall Square. Business signage and awnings are seen on the building. In the foreground is a street light. The sign on the building reads, The Old Corner built 1690 8 1/2 x 10 3/4 Photographs